2016
DOI: 10.1159/000448219
|View full text |Cite
|
Sign up to set email alerts
|

Enzalutamide as a Fourth- or Fifth-Line Treatment Option for Metastatic Castration-Resistant Prostate Cancer

Abstract: Objective: To evaluate the efficacy of enzalutamide (Enz) as fourth- or fifth-line treatment in men with metastasized castration-resistant prostate cancer (mCRPC), by analyzing a retrospective cohort of heavily pretreated patients. Methods: We evaluated toxicity, overall survival (OS), progression-free survival (PFS) and time to prostate-specific antigen (PSA) progression data from 47 CRPC patients treated with fourth- or fifth-line Enz. Results: All patients were treated with docetaxel and abiraterone acetate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 24 publications
0
4
1
Order By: Relevance
“…Significantly longer PFS and OS, more frequent PSA response, and less fatigue are observed with earlier lines of enzalutamide in the real-life setting. In comparison to our 19% PSA response and PFS of 2.2 months (95% CI, 1.7-4.0 months) for 3L or 4L enzalutamide, Badraising et al 24 reported an even more favorable PSA response rate of 23% and PFS of 12.1 weeks (95% CI, 9.9-14.0 weeks) for 4L or fifth-line enzalutamide. Also, our results as mentioned concerning the line of treatment are consistent with those for the other AR-signaling pathway inhibitor, abiraterone, for Chinese populations.…”
Section: Discussioncontrasting
confidence: 78%
“…Significantly longer PFS and OS, more frequent PSA response, and less fatigue are observed with earlier lines of enzalutamide in the real-life setting. In comparison to our 19% PSA response and PFS of 2.2 months (95% CI, 1.7-4.0 months) for 3L or 4L enzalutamide, Badraising et al 24 reported an even more favorable PSA response rate of 23% and PFS of 12.1 weeks (95% CI, 9.9-14.0 weeks) for 4L or fifth-line enzalutamide. Also, our results as mentioned concerning the line of treatment are consistent with those for the other AR-signaling pathway inhibitor, abiraterone, for Chinese populations.…”
Section: Discussioncontrasting
confidence: 78%
“…Often, more than one intervention is used to suppress bone metastatic growth and maintain a patient's quality of life [65]. Although EBRT, bisphosphonate, and denosumab can reduce the onset of the painful complications of bone metastasis [17,18,[66][67][68][69][70][71], delivering EBRT to every bone metastatic lesion is not practical and bisphosphonate and denosumab fail to improve the overall survival of bone metastatic patients (since these therapies mainly target bone remodeling but not cancer cells within the bone). Because of these limitations, bone metastasis is currently considered a hard-to-treat disease.…”
Section: Treatment Of Bone Metastasesmentioning
confidence: 99%
“…Radium-223 dichloride ( 223 RaCl 2 : T 1/2 = 11.4 d; Eα max = 6-7 MeV) is a watersoluble salt that was approved nearly a decade ago by the FDA for the treatment of bone metastasis associated with metastatic prostate cancer. Similar to calcium ions, this alkaline earth ion accumulates in bone, where it decays through seven daughter radionuclides, while releasing four α ++ -particles and two β − -particles, generating approximately 30 MeV of total kinetic energy, which is deposited in the surrounding bone cancer microenvironment [67][68][69]78,113]. This large energy deposition is believed to generate irreparable double-stranded DNA breaks within the DNA of tumor cells that have localized in the bone, causing cancer cell death [114][115][116][117].…”
Section: Radiopharmaceuticals For Bone Metastasesmentioning
confidence: 99%
“…Sequential treatment with different AR-targeting agents has shown limited efficacy as exemplified by modest PSA responses when sequentially treated with enzalutamide and abiraterone or vice versa ( Loriot et al 2013 , Noonan et al 2013 , Bianchini et al 2014 , Schrader et al 2014 , Brasso et al 2015 , Cheng et al 2015 , Petrelli et al 2015 , Badrising et al 2016 a ). Furthermore, it is suggested that docetaxel has a reduced activity after prior therapy with enzalutamide or abiraterone ( Mezynski et al 2012 , Aggarwal et al 2013 , Suzman et al 2014 ).…”
Section: Beyond Enzalutamide Resistance – Therapy Sequencing and Altementioning
confidence: 99%